2010
DOI: 10.1590/s0034-71672010000500025
|View full text |Cite
|
Sign up to set email alerts
|

Liderança dialógica nas instituições hospitalares

Abstract: Trata-se de uma reflexão-teórica com o objetivo de discutir sobre a importância da inserção da liderança dialógica nas instituições hospitalares. O referencial teórico para fundamentar esta reflexão é de Paulo Freire complementado com outros autores. O modelo de liderança dialógica consiste em um instrumento gerencial que se difere dos métodos coercitivos e autocráticos, por ser fundamentado no estabelecimento de um processo comunicacional eficiente, capaz de estimular a autonomia, a co-responsabilização e a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 4 publications
0
7
0
18
Order By: Relevance
“…Rather, it refers to the meeting of individuals to discuss problems and situations aiming to transform reality (25) . Dialogical leadership emerges as the ability of a leader to influence his/her collaborators to act critically and reflectively upon their practice through the establishment of an efficient communication process, and can contribute and encourage changes in micro and macro spaces where the nursing team acts, as well as encouraging autonomy, co-responsibility, and valorization of workers and users of health services (26) .…”
mentioning
confidence: 99%
“…Rather, it refers to the meeting of individuals to discuss problems and situations aiming to transform reality (25) . Dialogical leadership emerges as the ability of a leader to influence his/her collaborators to act critically and reflectively upon their practice through the establishment of an efficient communication process, and can contribute and encourage changes in micro and macro spaces where the nursing team acts, as well as encouraging autonomy, co-responsibility, and valorization of workers and users of health services (26) .…”
mentioning
confidence: 99%
“…(13) The professional nurse needed to share certain skills to work in management of the service, bearing in mind that the manager is considered to be a reference for staff members, for the other professionals from other areas, as well as for the users. (14) The results showed that the research subjects expected that the manager could integrate the nursing staff when performing activities, promoting a healthy environment for work, with the establishment of bonds of trust and reduction of conflicts. Thus, it was important that the nurse, in a conflictual situation, demonstrated consistent conduct, was proactive, flexible and adopted strategies to manage such events.…”
Section: Discussionmentioning
confidence: 97%
“…Algumas pessoas tentam camuflar fraquezas e inseguranças por meio da prepotência e da arrogância ao lidar com os membros da equipe (20) . Assim, o medo torna-se uma forma de repressão, que pode induzir as pessoas a aceitarem tal influência.…”
Section: àS Vezes Rola Tensão Entre a Equipe Algum Estresse Mesmo Counclassified
“…Situações como essa podem ocasionar grandes problemas nas organizações, desencadeando conflitos e interferindo de modo negativo no clima de trabalho. A falta de diálogo entre os membros da equipe de enfermagem e o silêncio frente a esse tipo de problema podem desgastar os profissionais e propiciar ambientes laborais pouco saudáveis (20) .…”
Section: àS Vezes Rola Tensão Entre a Equipe Algum Estresse Mesmo Counclassified